ESTIMATION OF GENETIC VARIABILITY, HERITABILITY, AND GENETIC ADVANCE FOR YIELD AND YIELD CONTRIBUTING CHARACTERS IN SORGHUM (SORGHUM BICOLOR L.) - KHANDEBHARAD PR; POLE SP; MUNDHE SS; GAIWAL KB; MALI BB (Innovare Journal of Agricultural Sciences, 2024)
The field experiment was conducted at the Experimental Farm of College of Agriculture, Latur, during Kharif – 2021–2022 with 26 genotypes of Sorghum, including three checks genotypes as PVK-1009-C, PVK-400-C, and PVK-809-C, with the goal of studying genetic variability, heritability, and genetic advance for yield and yield contributing characters in Sorghum (Sorghum bicolor L.). An analysis of variance involving 26 Sorghum genotypes for 12 quantitative characters revealed significant differences for all the traits under study indicating the presence of wide genetic variability in the experimental materials. Fodder yield per plant field grade score, plant height, grain yield per plant, threshed grade score, and test weight had a significantly high genotypic coefficient of variation (GCV) and phenotypic coefficient of variation magnitudes. The present investigation clarified that plant height, number of grains per primary, field grade score, threshed grade score, grain yield per plant, and fodder yield per plant these character have high heritability coupled with a high genetic advance and high GCV, indicating the role of additive genes in governing the inheritance of these traits, which could be improved through simple selection.